Effectiveness of Using Learning Modules Based on Communicative Approaches in Improve Arabic speaking skills in Specialization Classes - Fadzilah, Nurul; Amrullah, Abdul Malik Karim; Kholil, Ahmad; Huda, Ahmad Nawirul; Al Faruqi, Mhd Ibnu Hannan (Jurusan Pendidikan Bahasa Arab, 2025)
This study aims to develop an Arabic language teaching module based on a communicative approach to improve speaking skills in the Arabic specialization class. Based on observations and interviews conducted, it was found that Arabic learning in the specialization class still uses the same textbooks as regular classes, and the teaching method primarily relies on lectures. Furthermore, teachers have not yet used a specific teaching module that aligns with the needs of the specialization class. The research method employed is Research and Development (R&D), using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Based on the calculation of the N-gain score, the average value obtained was 0.7, which falls into the high category, with an improvement percentage of 75%, interpreted as fairly effective. In addition, the results of the paired sample t-test showed a significance value (2-tailed) of 0.01, which is less than 0.05. Therefore, the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. This indicates a significant difference between students pretest and posttest scores after using the module. The findings of this study indicate that the communicative approach-based teaching module is highly effective in improving the speaking skill of students in the specialization class. It is recommended that teachers utilize and integrate this module into the learning process to create an active, interactive, and efficient learning environment.